An investigation into nineteenth century book illustration with reference to the movement towards total collaboration in the works of Charles Dickens and his major illustrators - Crowe, Richard J J (Rhodes University, Faculty of Humanities, Department of Fine Art, 1980)
It is necessary to state clearly at the outset of this essay that the field comprising Book Illustration is extremely complex. This is not difficult to appreciate when one considers that the term "Book Illustration" covers both the highly developed art forms such as are found for example in the Book of Kells; and at the same time such cheap and shallow examples as are found in magazines and books that are churned out for the million. Therefore it becomes necessary to draw a sharp distinction between what could be called "inferior" and "superior" quality of Book Illustration. (a) I see this dividing line being drawn between two fundamentally divergent attitudes: the one involves a purely external and decorative approach which lacks real artistic value; (b) and the other, which is the result of the dynamic collaboration between an author and an artist to produce work founded on deep and rich artistic principles. (c) For the sake of clarity I wish to take this idea of a division a step further, and to suggest that within the "superior" bracket there is also a continuing scale of improvement and bettering, which culminates in an idealised state which could be called "TOTAL COLLABORATION" between an author and an artist.
Keywords: Dickens, Charles, 1812-1870 -- Illustrations; Illustrators; llustration of books -- Great Britain -- 19th century